Long-Term Effects of Chronic Buspirone during Adolescence Reduce the Adverse Influences of Neonatal Inflammatory Pain and Stress on Adaptive Behavior in Adult Male Rats - Butkevich, Irina P.; Mikhailenko, Viktor A.; Vershinina, Elena A.; Aloisi, Anna M.; Barr, Gordon A. (Frontiers in Behavioral Neuroscience, 2017)
Neonatal pain and stress induce long-term changes in pain sensitivity and behavior. Previously we found alterations in pain sensitivity in adolescent rats exposed to early-life adverse events. We tested whether these alterations have long-lasting effects and if those effects can be improved by the 5-HT1A receptor agonist buspirone injected chronically during the adolescent period. This study investigates: 1) effects of inflammatory pain (the injection of formalin into the pad of a hind paw) or stress (short maternal deprivation-isolation), or their combination in 1-2-day-old rats on the adult basal pain, formalin-induced pain, anxiety and depression; 2) effects of adolescent buspirone in adult rats that experienced similar early-life insults. Changes in nociceptive thresholds were evaluated using the hot plate and formalin tests; levels of anxiety and depression were assessed with the elevated plus maze and forced swim tests respectively. Both neonatal painful and stressful treatments induced long-term alterations in the forced swim test. Other changes in adult behavioral responses were dependent on the type of neonatal treatment. There was a notable lack of long-term effects of the combination of early inflammatory pain and stress of maternal deprivation-isolation on the pain responses, anxiety levels or on the effects of adolescent buspirone. This study provides the first evidence that chronic injection of buspirone in adolescent rats alters antinociceptive and anxiolytic effects limited to adult rats that showed behavioral alterations induced by early-life adverse treatments. These data highlight the role of 5-HT1A receptors in long-term effects of neonatal inflammatory pain and stress of short maternal deprivation-isolation on adaptive behavior and possibility of correction of the pain and psychoemotional behavior that were altered by adverse pain/stress intervention using buspirone during critical adolescent period.